2009
DOI: 10.1117/1.3251013
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative optical spectroscopy can identify long-term local tumor control in irradiated murine head and neck xenografts

Abstract: Noninvasive and longitudinal monitoring of tumor oxygenation status using quantitative diffuse reflectance spectroscopy is used to test whether a final treatment outcome could be estimated from early optical signatures in a murine model of head and neck cancer when treated with radiation. Implanted tumors in the flank of 23 nude mice are exposed to 39 Gy of radiation, while 11 animals exposed to sham irradiation serve as controls. Diffuse optical reflectance is measured from the tumors at baseline (prior to ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 11 publications
6
46
0
Order By: Relevance
“…Vishwanath et al recently demonstrated the potential clinical relevance of this technique by showing that early changes in oxygenation in response to radiation treatment are predictive of local tumor control in a xenograft model (229). Further, in another study, the non-invasive monitoring of intra-tumor drug concentration using fluorescence diffuse reflectance spectroscopy predicted the tumor response to doxorubicin in vivo (165).…”
Section: Non-invasive Hypoxia Imagingmentioning
confidence: 99%
“…Vishwanath et al recently demonstrated the potential clinical relevance of this technique by showing that early changes in oxygenation in response to radiation treatment are predictive of local tumor control in a xenograft model (229). Further, in another study, the non-invasive monitoring of intra-tumor drug concentration using fluorescence diffuse reflectance spectroscopy predicted the tumor response to doxorubicin in vivo (165).…”
Section: Non-invasive Hypoxia Imagingmentioning
confidence: 99%
“…Even though there have been several longitudinal therapy monitoring studies on animal cancer models with diffuse optical spectroscopy [51,60] and/or diffuse correlation spectroscopy [61,62], this study has several unique and noteworthy aspects in the study design, data analysis method, and findings. First, the tumor model based on orthotopically implanted syngeneic tumors was chosen since it is regarded to be more predictive of responses than ectopic tumors [63].…”
Section: Significancementioning
confidence: 99%
“…11,51,52,54 The overall strategy of diffuse reflectance and fluorescence spectroscopy using our scalable inverse Monte Carlo models is to ultimately provide a powerful tool to quantitatively, rapidly and non-destructively examine bioenergetics of living tissues and in particular, cancers by simultaneously being able to report on the three axes of energy production: vascular oxygenation, mitochondrial activity (TMR), and glycolysis (2-NBDG, NADH).…”
Section: Discussionmentioning
confidence: 99%